2011
DOI: 10.18632/aging.100325
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the BRCT binding site of BRCA1 result in hyper-recombination

Abstract: We introduced a K1702M mutation in the BRCA1 BRCT domain known to prevent the binding of proteins harboring pS-X-X-F motifs such as Abraxas-RAP80, BRIP1, and CtIP. Surprisingly, rather than impairing homologous recombination repair (HRR), expression of K1702M resulted in hyper-recombination coinciding with an accumulation of cells in S-G2 and no effect on nonhomologous end-joining. These cells also showed increased RAD51 and RPA nuclear staining. More pronounced effects were seen with a naturally occurring BRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(88 citation statements)
references
References 54 publications
5
82
0
1
Order By: Relevance
“…On the other hand, silencing BRCA1, BRIP1 or CtIP resulted in decreased HR, suggesting that HHR is dependent on the presence of BRCA1, and that the disruption of interactions within the BRCA1-A complex is the critical step resulting in these effects. 24,25 Together, these three reports concluded that disruption of BRCT interactions, whether resulting from mutations in the BRCT domain or from specifically preventing the A complex from binding to the BRCT domain, resulted in HHR [24][25][26] ( Fig. 1A and C).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…On the other hand, silencing BRCA1, BRIP1 or CtIP resulted in decreased HR, suggesting that HHR is dependent on the presence of BRCA1, and that the disruption of interactions within the BRCA1-A complex is the critical step resulting in these effects. 24,25 Together, these three reports concluded that disruption of BRCT interactions, whether resulting from mutations in the BRCT domain or from specifically preventing the A complex from binding to the BRCT domain, resulted in HHR [24][25][26] ( Fig. 1A and C).…”
Section: Introductionmentioning
confidence: 83%
“…Two reports examined the effects of silencing BRCT-interacting proteins, while a third examined the effect of mutating the binding pocket of the BRCT domain to prevent these interactions, with all reaching similar conclusions. [24][25][26] Silencing Abraxas, RAP80 or the BRCC36 deubiquitinase, all part of the A complex, resulted in increased or hyper-HR (HHR). Similarly, synthetic (K1702M) and naturally occurring (M1775R) mutants of BRCA1 that disrupt most, if not all, BRCT pS-X-X-F-binding interactions also resulted in aberrant HHR.…”
Section: Introductionmentioning
confidence: 99%
“…However, the process of DNA repair itself can create mutations, insertions, deletions and base replacements. For example, mutations can occur due to inappropriately high levels of a repair mechanism which normally suppresses tumorigenesis-mitotic recombination and hyper-recombinationwhich has recently been linked to mutations in BRCA1 but is also likely to occur due to other defects in DNA damage repair genes [28][29][30] . Gross DNA lesions and chromosomal abnormalities can be induced by DNA replication stress.…”
Section: Endogenous Assaultsmentioning
confidence: 99%
“…One important gene [59] ; and (2) an N-terminal RING domain which interacts with BARD1 protein to allow for E3 ubiquitinligase activity [60][61][62] . The BRCT domain contains repeats which bind to unique phosphor-serine motifs of other proteins and which allow participation in DNA damage checkpoint and double strand break repairs [30,42,59,63] . BRCT domains are also found in other breast-cancerrelated genes such as XRCC4 or FANCG.…”
Section: Defects In Dna Repair Pathways Associated With Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation